“How I became what I am”: an aesthetics of twist cinema in films from the 1960s and 1970s - Bessa, Karla Adriana Martins Bessa Adriana Martins (Revista Estudos Feministas, 2017)
The article analyzes the political and theoretical potential of cinematographic language to express and rebuild the relationship between sexual and gender differences. As cultural products, the three films analyzed - A Casa Assassinada (1972), Sunday, bloody Sunday (1971) and Les Amities Particulières (1964) - allude to feminist issues of the time, as well as instigating a reading of gender beyond the narratives, by historicizing the visibility of the female body, heteronormativity, and the subversiveness of forbidden loves as represented through the films’ structure. The text argues, from a queer perspective, that the aesthetic nature of twist cinema, within the limits of each style and period, was precisely the boldness to run risks in its visual grammar, not making political concessions in challenging the moral canons of current society.